Icariin-Loaded Hydrogel Regulates Bone Marrow Mesenchymal Stem Cell Chondrogenic Differentiation and Promotes Cartilage Repair in Osteoarthritis - Zhu, Yuefeng; Ye, Le; Cai, Xiaoxi; Li, Zuhao; Fan, Yongqian; Yang, Fengjian (Frontiers in Bioengineering and Biotechnology, 2022)
Intra-articular injection of mesenchymal stem cells is a potential therapeutic strategy for cartilage protection and symptoms relief of osteoarthritis (OA). However, controlling chondrogenesis of the implanted cells in the articular cavity remains a challenge. In this study, hydrogels containing various concentrations of icariin were prepared by in situ crosslinking of hyaluronic acid and Poloxamer 407. This injectable and thermoresponsive hydrogels sustain good biocompatibility for chondrocytes and bone marrow mesenchymal stem cells (BMSCs), as well as induce proliferation and chondrogenesis of BMSCs through the Wnt/β-catenin signaling pathway. Intra-articular injection of this BMSCs loaded composite hydrogels can significantly prevent cartilage destruction by inducing stem cells into chondrogenic differentiation, and relieve pain through regulating the expression of inflammatory cytokines, e.g., IL-10 and MMP-13 in the cartilages in OA model. Incorporating BMSCs into this novel icariin-loaded hydrogel indicate a more superior efficacy than the single BMSCs injection, which suggesting a great potential for the application in OA.